Birth outcomes between 22 and 26 weeks' gestation in national population‐based cohorts from Sweden, England and France. (12th September 2021) - Morgan, Andrei S.; Zeitlin, Jennifer; Källén, Karin; Draper, Elizabeth S.; Maršál, Karel; Norman, Mikael; Serenius, Fredrik; van Buuren, Stef; Johnson, Samantha; Benhammou, Valérie; Pierrat, Véronique; Kaminski, Monique; et al.
Abstract: Aim: We investigated the timing of survival differences and effects on morbidity for foetuses alive at maternal admission to hospital delivered at 22 to 26 weeks' gestational age (GA). Methods: Data from the EXPRESS (Sweden, 2004–07), EPICure‐2 (England, 2006) and EPIPAGE‐2 (France, 2011) cohorts were harmonised. Survival, stratified by GA, was analysed to 112 days using Kaplan‐Meier analyses and Cox regression adjusted for population and pregnancy characteristics; neonatal morbidities, survival to discharge and follow‐up and outcomes at 2–3 years of age were compared. Results: Among 769 EXPRESS, 2310 EPICure‐2 and 1359 EPIPAGE‐2 foetuses, 112‐day survival was, respectively, 28.2%, 10.8% and 0.5% at 22–23 weeks' GA; 68.5%, 40.0% and 23.6% at 24 weeks; 80.5%, 64.8% and 56.9% at 25 weeks; and 86.6%, 77.1% and 74.4% at 26 weeks. Deaths were most marked in EPIPAGE‐2 before 1 day at 22–23 and 24 weeks GA. At 25 weeks, survival varied before 28 days; differences at 26 weeks were minimal. Cox analyses were consistent with the Kaplan‐Meier analyses. Variations in morbidities were not clearly associated with survival. Conclusion: Differences in survival and morbidity outcomes for extremely preterm births are evident despite adjustment for background characteristics. No clear relationship was identified between early mortality and later patterns of morbidity.